Tensions for a decolonial shift in communicological thinking. Opening the discussion - Karam, Tanius (2016)
This paper aims at discussing the relation between the decolonial studies (ED) and communication studies (EC). There’s an intention to develop some explanatory exercises: analyze the need of inquiring on the expression “critical schools in communication”; highlighting some debates that summarize the differences between EDs and cultural studies in communication; finally interrogating the epistemology of communication as a way to address not just the questions of some of the communication narratives or traditions, but the manner and consequences of that answer.